Rare presentation of adenomatoid odontogenic tumor in a pediatric patient: a case report - Bonardi, João Paulo [UNESP]; da Costa, Fernanda Herrera; Matheus, Ricardo Alves; Ito, Fabio Augusto; Pereira-Stabile, Cecilia Luiz (Springer Nature, 2016)
The adenomatoid odontogenic tumor (AOT) is a painless benign tumor with slow growth, usually asymptomatic. It has three variants: follicular, extrafollicular, and peripheral. In the follicular type, the tumor is associated with an impacted tooth, and maxillary canines are the most frequently affected. Association with primary teeth is very rare. Treatment consists essentially in a total lesion enucleation. The objective of this paper is to present the clinical case of a 7-year-old female patient with an adenomatoid odontogenic tumor associated with the crown of the left lower deciduous canine (73), dislodging it to the mandibular base and consequently shifting and also impacting the permanent lower canine (33). The lesion was treated with careful enucleation, preserving the permanent canine, which then had its eruption path released favoring its migration to an ideal position.
Keywords: Adenomatoid odontogenic tumor; Deciduous tooth; Impacted tooth; Pediatric Dentistry